Efektivitas Media Geometry Rotation Wheel untuk Pengenalan Bentuk Geometri pada Anak Disabilitas Intelektual - Sari Wulandari; Setia Budi; Marlina Marlina; Syari Yuliana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the low ability to recognize geometric shapes (triangles, quadrilaterals, and circles) in students with intellectual disabilities. This study aims to analyze the effect of using the Geometry Rotation Wheel media on the ability to recognize geometric shapes. The study used a quantitative approach with the Single Subject Research (SSR) method with an A-B-A design on one fourth-grade student at SLBN 1 Muaro Sijunjung. Data were collected through performance tests and analyzed using visual analysis within and between conditions. The results showed an increase in the ability to recognize geometric shapes as indicated by an increase in the mean level from 22 in the first baseline phase (A1) to 70.75 in the intervention phase (B), and reaching 100 in the second baseline phase (A2). Visual analysis also showed a tendency for increasing data with an overlap percentage of 0% in the A1-B phase and 37.5% in the B-A2 phase, indicating a functional relationship between the intervention and changes in the subject's abilities. These findings indicate that the Geometry Rotation Wheel can be used as a learning medium that supports the recognition of geometric shapes in students with intellectual disabilities and is an alternative media that can be utilized by teachers in mathematics learning in special education.